Symbole religijne i metafory mądrościowe Laozi (Przegląd Religioznawczy – The Religious Studies Review, 2019)
There are both religious symbols and wisdom metaphors in Dao De Jing by Laozi. They suggest that the ultimate reality is above the human intellect. The most important metaphor is Dao – “Way”. The metaphor of “the mother” of the world plays a very important role. This metaphor suggests that wisdom consists in penetrating the source of all being. The metaphor of the “Heaven Gates”, which indicates the transition from common sense to the supernatural. The metaphor of “the child” suggests that wisdom is not about accumulating knowledge, but on spiritual integration. The metaphor of yin, or metaphysical femininity, plays a very important role.